Signature whistles in wild bottlenose dolphins : Long-term stability and emission rates - Luís, Ana Rita (2016)
Whistles are key elements in the acoustic repertoire of bottlenose dolphins. In this species, the frequency contours of whistles are used as individual signatures. Assessing the long-lasting stability of such stereotyped signals, and the abundant production of non-stereotyped whistles in the wild, is relevant to a more complete understanding of their biological function. Additionally, studying the effects of group size and activity patterns on whistle emission rate may provide insights into the use of these calls. In this study, we document the decades-long occurrence of whistles with stereotyped frequency contours in a population of wild bottlenose dolphins, resident in the region of the Sado estuary, Portugal. Confirmed stereotypy throughout more than 20 years, and positive identification using the signature identification (SIGID) criteria, suggests that the identified stereotyped whistles are in fact signature whistles. The potential roles of non-stereotyped whistles, which represent 68 % of all whistles recorded, are still unclear and should be further investigated. Emission rates were significantly higher during food-related events. Finally, our data show a comparatively high overall whistle production for this population, and no positive correlation between group size and emission rates, suggesting social or environmental restriction mechanisms in vocal production.